2017
DOI: 10.1002/eap.1632
|View full text |Cite
|
Sign up to set email alerts
|

Using species traits to predict detectability of animals on aerial surveys

Abstract: Abstract. In animal surveys, detectability can vary widely across species. We hypothesized that detectability of animals should be a function of species traits such as mass, color, and mean herd size. We also hypothesized that models of detectability based on species traits can be used to predict detectability for new species not in the original data set, leading to substantial benefits for ecology and conservation. We tested these hypotheses with double-observer aerial surveys of 10 mammal species in northern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…Sólymos et al (81) and Johnston et al (82) found that body size was a significant predictor of bird species' detectability. There is also support that group size can influence detectability of animals (83). Although difficult to quantify, it is thought that the coloration of an organism influences its detectability (84).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sólymos et al (81) and Johnston et al (82) found that body size was a significant predictor of bird species' detectability. There is also support that group size can influence detectability of animals (83). Although difficult to quantify, it is thought that the coloration of an organism influences its detectability (84).…”
Section: Methodsmentioning
confidence: 99%
“…1 A ) is likely to be influenced by a suite of species’ life history traits. Previous work has shown that species traits (e.g., body size, color, and group size) can influence the detectability of a species ( 79 84 ), and thus in turn, the likelihood a species is recorded in a citizen science dataset ( 85 ). Sólymos et al ( 81 ) and Johnston et al ( 82 ) found that body size was a significant predictor of bird species’ detectability.…”
Section: Methodsmentioning
confidence: 99%
“…. RSO detection of 'available' animals depends on a range of 'environmental factors' such as animal size, group size, vegetation cover, species coloration, reaction to the aircraft, occurrence in multi-species assemblages; 'survey factors' such as flying height, counting strip-width and sun angle; and 'observer factors' such as experience and level of fatigue (Caughley et al 1976;Anderson and Lindzey 1996;Jachmann 2002;Melville et al 2008;McConville et al 2009;Wal et al 2011;Ransom 2012;Griffin et al 2013;Jacques et al 2014;Strobel and Butler 2014;Lubow and Ransom 2016;Schlossberg et al 2016;Schlossberg et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Trait-based models of population dynamics investigated the responses of populations to environmental changes (Santini et al, 2016) and to perturbations (Ozgul et al, 2012). Using an approach similar to that of the time-todetection studies mentioned in section 1.2 (Trait-based models of species distributions), Schlossberg et al (2018) modelled detectability for ten mammal species. This model was based on species traits such as body mass, mean herd size and color and employed a statistical approach based on conditional likelihoods.…”
Section: Trait-based Modelling Of Animals In Terrestrial Ecosystemsmentioning
confidence: 99%